Three new species of Pyricularia are isolated as zingiberaceous endophytes from Thailand - Bussaban B. (2014)
Pyricularia costina and three undescribed Pyricularia species were found as endophytes on wild ginger Amomum siamense and Alpinia malaccensis in Doi Suthep-Pui National Park, Chiang Mai, Thailand. Three new species, Pyricularia kookicola, P. longispora, and P. variabilis are described, illustrated and compared to similar Pyricularia species.